Friction riveting of TI-6AL-4V and pultruded glass fiber reinforced thermoset polyester hybrid joints - Borba, Natascha Zocoller (2015)
Friction Riveting is an innovative spot joining technology for metal-polymer hybrid structures. This MSc thesis provided for the first time in the literature, a fundamental understanding on the Friction Riveting process for metal-thermoset composites joints. Joints of Ti-6Al-4V rivet and pultruded glass fiber reinforced thermoset polyester part were produced under three joining conditions with different heat input. Thorough analytical techniques were used to understand the physics of the process and the effect of the energy input on the final microstructure of the joined parts, the physico-chemical changes in the composite and the local and global mechanical properties of the joints. The process temperature reached values up to 761 ± 2°C indicating intrinsic degradation of the composite, formation of a softened/molten glass interlayer between the rivet and the composite and complex metallurgical transformations in the metallic rivet. Through monitoring of the process temperature and torque, an unstable friction regime was observed for FricRiveting of pultruded thermoset composites leading to distinguished extents of composite degradation. The microstructure of the Ti-6Al-4V alloy changed across the length of the rivet, from the equiaxed morphology to acicular structures in the rivet tip, where plastic deformation occurred. Three microstructural zones were proposed for each joint part including two thermo-mechanically affected zones and a heat affected zone. Microhardness mapping was performed in the metallic rivet evidencing an increase from the center to the tip of the rivet, with a hardness increment of over 20% compared to the base material (HVTi6Al4V= 300- 320 HV). The glass interphase consolidated in the metallic surface reached values of up to 974 HV followed by a drastic decrease to 24 HV in the polyester matrix located out of the joint area. The ultimate bearing strength ranged between 60 MPa and 166 MPa. Lesser composite degraded areas led to stronger joints. Two failure modes were observed combining initial composite bearing followed by final failure through shear of the rivet with partial rivet pullout or by full rivet pull-out. Complex failure micro-mechanisms were observed including the combination of cohesive and adhesive failures through the glass layer and the damaged composite interface. Friction-riveted joints achieved an ultimate lap shear strength of up to 80% to that of a similar bolted joint. A case study for a presumptive truss bridge application of friction-riveted joints showed a necessary of 92 rivets per truss node, 43% less than previous studies and with potential for further optimization.